2019
DOI: 10.3390/jcm8040509
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Evaluation of 25 Proximal and Distal Risk-Factors for Gambling-Related Harm

Abstract: Individual differences in the risk of developing gambling-related harm play an important role in theoretical models and practical interventions. The present study attempted comprehensive measurement and evaluation of 25 known risk factors for gambling-related harm in order to determine which factors provided large and unique explanatory power. We surveyed 1650 regular gamblers from an online panel, screening in 1174 (466 male) who passed all checks of attention and response consistency. We evaluated each risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 42 publications
(50 reference statements)
8
77
1
Order By: Relevance
“…Despite not including data on play frequency four highly rated studies suggest that living in an urban area, having a low income, less feelings of school connectedness, or being unemployed predicted more harms from gambling 41,46,55,66 . And while three studies reported little or no signi cant differences 46,54,56 , Melendez-Torres et al 52 reported that more a uent participants had more harms with a higher frequency of play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite not including data on play frequency four highly rated studies suggest that living in an urban area, having a low income, less feelings of school connectedness, or being unemployed predicted more harms from gambling 41,46,55,66 . And while three studies reported little or no signi cant differences 46,54,56 , Melendez-Torres et al 52 reported that more a uent participants had more harms with a higher frequency of play.…”
Section: Discussionmentioning
confidence: 99%
“…Browne et al 54 found that age had no impact on harm pro les, and Lloyd et al 55 found no association between age and gambling-induced thoughts of self-harm. Browne et al 56 found that although younger age appeared to correlate with harm this was not statistically signi cant, and 43 reported that guilt was not associated with age. Goh et al 57 found that verbal abuse was most common from young males, however older males were more likely to coerce money from their spouse.…”
Section: Agementioning
confidence: 97%
“…Eighteen studies include data on age, and several of these found that being younger was associated with a higher risk of experiencing gambling harms [40,41,42,43,33,44] . In particular one study found that younger age groups (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were at risk of dependence and social harms [45] , however some studies found younger gamblers were less at risk of financial harms [46,47] , despite one suggesting that they spent more [48] .…”
Section: Agementioning
confidence: 99%
“…Fifteen studies examined gender, and few of these found any evidence that harms affected men and women differently [53,21,40,41] . Where differences were found these could be Health Inequality in Gambling -17 explained by other factors, such as studies that show men have a higher prevalence of harms than women [42,43,54] , being explained by men gambling more frequently than women and spending more money when gambling [45,47,55] .…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation